A path integral molecular dynamics study on intermolecular hydrogen bond of acetic acid–arsenic acid anion and acetic acid–phosphoric acid anion clusters. Issue 1 (9th October 2018) - Kawashima, Yukio; Sawada, Keisuke; Nakajima, Takahito; Tachikawa, Masanori
Abstract : We apply ab initio path integral molecular dynamics simulation employing ωB97XD as the quantum chemical calculation method to acetic acid–arsenic acid anion and acetic acid–phosphoric acid anion clusters to investigate the difference of the hydrogen bond structure and its fluctuation such as proton transfer. We found that the nuclear quantum effect enhanced the fluctuation of the hydrogen bond structure and proton transfer, which shows treatment of the nuclear quantum effect was essential to investigate these systems. The hydrogen bond in acetic acid–arsenic acid anion cluster showed characters related to low‐barrier hydrogen bonds, while acetic acid–phosphoric acid anion cluster did not. We found non‐negligible distinction between these two systems, which could not be found in conventional calculations. We suggest that the difference in amount of atomic charge of the atoms consisting the hydrogen bond is the origin of the difference between acetic acid–arsenic acid and acetic acid–phosphoric acid anion cluster. © 2018 Wiley Periodicals, Inc. Abstract : Ab initio path integral molecular dynamics simulation is applied to acetic acid–arsenic acid anion and acetic acid–phosphoric acid anion clusters to investigate the difference of the hydrogen bond structure and its fluctuation. Analysis was performed for various clusters with different numbers of hydrogen bonds. The hydrogen bond in the acetic acid–arsenic acid anion cluster showed characters related to low‐barrier hydrogen bonds, while acetic acid–phosphoric acid anion cluster did not. The authors found non‐negligible distinction between these two systems.